Pengembangan Keterampilan Sosial Siswa Sekolah Dasar dalam Konteks Pendidikan Multikultural Pada Mata Pelajaran IPS - Saputra, Erwin EKa (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Multicultural education in primary schools plays an important role in shaping students' social skills. It teaches students to appreciate cultural, ethnic, religious and linguistic diversity in daily life. This article aims to discuss how primary school students' social skills are developed through a multicultural education approach. Using various teaching methods and school programmes, multicultural education helps students understand the values of tolerance, cooperation and empathy. The study found that students exposed to multicultural education showed significant improvements in social skills, such as openness to differences and the ability to work in diverse groups.